Effect of the production or use of mixtures of bakers or brewers yeast extracts on their ability to promote growth of lactobacilli and pediococci - Champagne,Claude P (Pontificia Universidad Católica de Valparaíso, 2003)
Three brewers and three bakers yeast extracts (YE) were obtained from five commercial suppliers. They were added to microbiological media and their growth-promoting properties were examined using four lactic cultures (Lactobacillus casei EQ28 and EQ85, Lactobacillus acidophilus EQ57, Pediococcus acidilactici MA18/5-M). Bakers YE have a higher total nitrogen content than brewers YE, but there was not always a correlation between the nitrogen content and growth. A systematic preference for bakers YE over brewers YE was only encountered with Lb. casei EQ85, but the other lactic cultures had variable reactions to the source of YE. With Lb. casei EQ85 and Pc. acidilactici 17/5M, mixing of the two sources of YE gave progressively higher growth as a function of the content of the better YE. With Lb. acidophilus EQ57 and Lb. casei EQ28, however, there were instances where a mixture of 75% brewers YE with 25% bakers YE gave biomass levels higher than those obtained with the pure products. A series of autolyses were conducted with mixtures of brewers and bakers yeast, to see if the YE obtained differed from those obtained from autolysis of the individual yeast cultures. Brewers yeast autolysates had higher turbidity than those of bakers yeast. The maximum yield was obtained with the co-autolysis of a combination of 60% bakers yeasts and 40% brewers yeasts. Growth of Lb. acidophilus EQ57 was best in the autolysate obtained from 100% brewers yeast, in spite of the higher nitrogen content of YE produced when bakers yeast was used during co-autolysis.